Leukocytes Profil of Monopterus albus raired in Biofloc System with Different Stock Densities - Ahmad, Nurkholis; Lukistyowati, Iesje; Riauwaty, Morina (Jurnal Akuakultur SEBATIN, 2024)
Biofloc is an agglomerate composed of various autotrophic and heterotrophic organisms as well as particles, which are mixed by aeration and circulation to form clumps that integrate quite well in water. This research was carried out in March- May 2021 in the Hatcheries and Experimental Ponds and Parasites and Fish Diseases Laboratory, Faculty of Fisheries and Marine, Universitas Riau. The study aimed to analyze the leukocyte profile of the Monopterus albus raired biofloc system with different stock densities. The research method used a one-factor, completely randomized design (CRD) with four treatments with three replications. The treatments applied were P1 (of 10 fish/25 L), P2 (of 20 fish/25 L), P3 (of 30 fish/25 L), and P4 (of 40 fish/25 L). M. albus were reared in a biofloc system for 40 days. The results showed that there was an effect of stock densities on the leukocyte profile of M. albus reared in biofloc systems with different stock densities, a significant effect (P<0.05). The best stock density was at P3 (30 fish/25 L), where the total leukocytes were 3.62 x 104 cells/mm3, leucocrite was 2.00%, phagocyte activity was 36.66%, while the percentage of lymphocytes was 83.00 %, monocytes was 16.00%, and neutrophils was 13.00%. Water quality during this study was at temperature 26-300C, pH 6-7, dissolved oxygen 4.4-6.8 mg/L, and ammonia 0.02-0.06 mg/L. It was concluded that there was an effect on the biofloc system of stock density on the leucocyte profile M. albus